SUBSYSTEM OF MODELS OF ECOLOGICAL MONITORING FOR ESTIMATION OF THE STATE OF ATMOSPHERIC AIR - Polischuk, S. Z.; Kaspijcteva, V. Y. (Science and Transport Progress, 2017)
Purpose. The article is devoted to the improvement of the method of forecasting the quality of atmospheric air when discharging from stationary sources of pollution and from mobile sources of pollution. The choice of the goal is due to the fact that recently the requirements to the quality of the forecast information of the atmospheric air have increased, which entails the modernization of existing forecast methods. The work has improved the unit for assessing and forecasting the state of atmospheric air in a system of regional environmental monitoring to improve the level of environmental safety in the planning and development of territories. The improved unit serves to determine the quality indices of atmospheric air and the state of its resource potential. Methodology. For the decision of the put task the complex method of researches, which consists in the analysis of the systems and generalization of existent researches after the problem of estimation and prognosis of the state of atmospheric air, use of objective method at the construction of the hierarchical system of models, is utilized. For determination of indexes the method of expert estimations is top level used. For the solution of differential equations of aerodynamics and mass transfer uses finite-difference methods. Findings. The structure of prognosis block is developed on atmospheric air in the system of the ecological monitoring. Researches of indexes of quality of atmospheric air and state of its resource potential are executed with the use of the developed models. Originality. The use of a hierarchical series of mathematical models for a comprehensive assessment and prediction of the state of atmospheric air in scenarios of socio-ecological and economic development and urban development activities of the regions is justified, which makes it possible to raise the level of their ecological safety at the stage of carrying out design and prospecting works. Practical value. The presented complex of models allows to estimate and forecast the state of atmospheric air in the system of environmental monitoring, taking into account the natural and climatic, socio-economic characteristics of the regions, their resource potential and integrated indicators of sustainable development of the territories. The proposed approach can be used in the monitoring system, both large megacities and small towns. It can serve as a tool for expert assessment of the implementation of various environmental measures in cities.